COMPARATIVE ANALYSIS OF THE UKRAINIAN AND POLISH STOCK MARKETS AMID GEOPOLITICAL TURBULENCE - Владислав Штак (Економіка та суспільство)
The full-scale invasion of Ukraine in February 2022 triggered a geopolitical shockwave that sent vastly different ripples through the capital markets of Ukraine and its immediate western neighbor, Poland. This paper presents a comparative analysis of the responses and subsequent performance of the Ukrainian and Polish stock markets, arguing that their divergent trajectories were dictated by two fundamental factors: existential threat and institutional anchoring. The Ukrainian market, represented by the PFTS Stock Exchange, executed a strategy of preservation through hibernation, with regulators immediately halting all trading and imposing strict capital controls to ensure state financial survival. This transformed the domestic capital market from a vehicle for private capital allocation into a direct instrument for sovereign financing via war bonds. In stark contrast, the Warsaw Stock Exchange (WSE) demonstrated resilience through adaptation. Despite initial volatility, its deep integration within the security and economic frameworks of NATO and the European Union provided a powerful institutional anchor, mitigating perceived risk and sustaining investor confidence. This stability allowed the Polish market not only to recover but to emerge as a strategic gateway for international investment and a proxy for speculation on Ukraine's eventual reconstruction. By examining market indices, regulatory actions, capital flows, and sectoral performance, this analysis challenges simplistic notions of geopolitical risk, revealing how institutional frameworks and strategic state intervention can fundamentally reshape market outcomes in times of profound crisis.